Sosialisasi dan Edukasi Pengelolaan Emosi melalui Media Botol Emosi kepada Mahasiswa - Diyayang Shinta Kharisma; Anggit Dyah Kusumastuti (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2025)
Emotional management issues among university students have become increasingly prevalent, particularly due to academic stress, social relationships, and direct personal burdens. Unfortunately, awareness of mental health and preventive emotional coping strategies remains limited. This community service project aimed to enhance students’ emotional awareness and self-regulation skills using a creative tool called the “Emotion Bottle.” The program was implemented through preparation, introduction, hands-on creation, and participatory evaluation stages. Results showed that most participants felt more emotionally connected after the activity and were able to identify emotions they had previously overlooked. The emotion bottle was perceived as engaging, easy to implement, and a meaningful, low-cost form of self-healing. This initiative is expected to serve as a simple psychological education model that can be replicated across youth and student communities).